AB0997 MATCHED CONTROLLED SURVEILLANCE OF TOCILIZUMAB TREATMENT FOR POLYARTICULAR JUVENILE IDIOPATHIC ARTHRITIS–AN INTERIM ANALYSIS. (June 2019) - Klein, Ariane; Conzelmann, Dennis; Hospach, Toni; Weller-Heinemann, Frank; Hansmann, Sandra; Kuemmerle-Deschner, Jasmin; Borte, Michael; Minden, Kirsten; Foeldvari, Ivan; Rietschel, Christoph; Ganser, Gerd; Trauzeddel, Ralf; et al.
Abstract : Background: Tocilizumab (TOC) is approved for treatment of polyarticular juvenile idiopathic arthritis (poly-JIA). Real world data are limited. Objectives: Long-term surveillance of patients newly initiating tocilizumab treatment for at least five years compared to a cohort of patients newly initiating a comparator biologic using the BIKER–registry. Methods: Baseline demographics, clinical characteristics and disease activity parameters as well as efficacy and safety parameters were compared between patients using TOC and a control cohort using alternative biologics. The cohorts were matched for region and date of therapy start. Efficacy outcome variables were JADAS10 and joint counts. Functional status was determined with the Childhood Health Assessment Questionnaire disability-index (CHAQ-DI). Safety assessments were based on adverse events (AE) reports. Results: Patients starting on TOC had a longer disease duration (5.2y vs. 2.9 y; p= 0.0001) and had TOC significantly more often as second line biologic than patients in the comparator group (80% vs 14%, p< 0.0001). No differences could be observed regarding disease activity parameters (JADAS 10 14.7 +/- 6.4 vs 15.8 +/- 6.0) or disability (CHAQ DI 0.65 +/- 0.63 vs 0.66 +/- 0.66) at baseline. Patients treated with TOC showed a substantial response to treatment with a significant reduction in JADAS 10 from 14.7 to 5.4 (p<0.0001). After 6 months of TOC treatment, 40% of patients had reached JADAS minimal disease activity (MDA), 22% of patients had reached JADAS remission. Tolerability was comparable between the two cohorts, with 31 in the TOC versus 34 patients in the control cohort experiencing AE; serious AE (SAE) were documented in 3 patients in the TOC and one patient in the control cohort. The SAE in the TOC cohort were medication intoxication with suicidal intent, JIA flare, gastrointestinal infection and abdominal pain in 1 patient each. In the control cohort there were JIA flare in 2 patients and gastrointestinal infection in 1 patient. No significant differences regarding infectious AEs, cytopenias or elevated transaminases were observed. No other AE were reported more than once; no deaths occurred. Conclusion: Comparability of efficacy was limited due to the fact that patients in the TOC cohort had longer disease duration and were more often second line biologic users. Tolerability was comparable in both cohorts. Long-term observation is ongoing. Disclosure of Interests: Ariane Klein: None declared, Dennis Conzelmann: None declared, Toni Hospach Speakers bureau: Chugai, Roche, Novartis, Frank Weller-Heinemann: None declared, Sandra Hansmann: None declared, Jasmin Kuemmerle-Deschner Grant/research support from: Jasmin Kuemmerle-Deschner is an employee of University of Tuebingen, Germany, and received consultants/speakers fees from Novartis and SOBI pharmaceuticals and grant support from SOBI and Novartis., Consultant for: Jasmin Kuemmerle-Deschner is an employee of University of Tuebingen, Germany, and received consultants/speakers fees from Novartis and SOBI pharmaceuticals and grant support from SOBI and Novartis., Speakers bureau: Jasmin Kuemmerle-Deschner is an employee of University of Tuebingen, Germany, and received consultants/speakers fees from Novartis and SOBI pharmaceuticals and grant support from SOBI and Novartis., Michael Borte Grant/research support from: Pfizer and Shire, Kirsten Minden Consultant for: AbbVie, Ivan Foeldvari Consultant for: Chugai, Novartis, Christoph Rietschel: None declared, Gerd Ganser: None declared, Ralf Trauzeddel: None declared, Markus Hufnagel: None declared, Dirk Foell Grant/research support from: not specified, Consultant for: not specified, Speakers bureau: not specified, Rainer Berendes: None declared, Gundula Boeschow: None declared, Prasad Oommen: None declared, Angelika Thon: None declared, Gerd Horneff: None declared